Application of Postharvest management of Corn to Support Integrated Farming System - Joko Nugroho Wahyu Karyadi; Dwi Ayuni; Nursigit Bintoro; Sri Rahayoe; Bambang Purwantana (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Corn is a superior crop and its production centers are in the Grobogan and Pati Regency, Central Java Province, Indonesia. This plant is partly cultivated in farm fields and forest land owned by Purwodadi Forest Control Area (in Indonesia known as 'Kawasan Penguasaan Hutan – KPH) as an intercrop during re-planting of tropical hardwood, namely teak. Corn has become one of the significant side hustles for most of the residents in KPH with high incomes. Unfortunately, this high corn production was not accompanied by adequate postharvest technology. Some vital problems occurred, especially during raining season, like fungi, undesired germination, and many more. Therefore, the weight loss of corn production is still very high. This activity aimed to assist farmers by changing how farmers look at the quality assurance of the produced corn products and improving farmers' postharvest corn practices. This activity's method was introducing corn harvesting machines, namely corn sheller machines, and improving the farmers’ knowledge about the quality control of corn. The activities were carried out to allocate five (5) units of corn sheller units to five Forest Village Community Institutions (in Indonesia known as 'Lembaga Masyarakat Desa Hutan,' LMDH) who were the targeted partners. The activities of sharing the knowledge regarding good postharvest for corn were going well and the participants gave excellent responses and actively participated.